2017
DOI: 10.1097/qad.0000000000001440
|View full text |Cite
|
Sign up to set email alerts
|

Increasing voluntary medical male circumcision uptake among adult men in Tanzania

Abstract: Objective:We evaluated a demand-creation intervention to increase voluntary medical male circumcision (VMMC) uptake among men aged 20–34 years in Tanzania, to maximise short-term impact on HIV incidence.Methods:A cluster randomized controlled trial stratified by region was conducted in 20 outreach sites in Njombe and Tabora regions. The sites were randomized 1 : 1 to receive either a demand-creation intervention package in addition to standard VMMC outreach, or standard VMMC outreach alone. The intervention pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 20 publications
1
34
1
Order By: Relevance
“…Data on the number, client age, and location of VMMCs performed were obtained from the trial data set. 34 Trial results showed that the total number of VMMC clients of all ages was higher in the intervention arms than in the control arms: 6251 vs. 3968, respectively (RR 1.4). Although the total number and proportion of clients aged 20–34 years were greater in the intervention arms, there was a non-significant difference in the proportion of men aged 20–34 years between intervention and control arms (11.3% vs. 14.7%, respectively) in Njombe, whereas a two-fold statistically-significant difference was observed in Tabora (27.5% vs. 11.5%).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Data on the number, client age, and location of VMMCs performed were obtained from the trial data set. 34 Trial results showed that the total number of VMMC clients of all ages was higher in the intervention arms than in the control arms: 6251 vs. 3968, respectively (RR 1.4). Although the total number and proportion of clients aged 20–34 years were greater in the intervention arms, there was a non-significant difference in the proportion of men aged 20–34 years between intervention and control arms (11.3% vs. 14.7%, respectively) in Njombe, whereas a two-fold statistically-significant difference was observed in Tabora (27.5% vs. 11.5%).…”
Section: Methodsmentioning
confidence: 95%
“…Details of the trial design and outcomes have been published. 34 The trial aimed to assess VMMC uptake among men aged 20–34 years following the locally-tailored demand creation strategy described compared with the standard of care normally delivered. Ten clusters were randomly selected per region and evenly allocated across control and intervention arms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These older males usually perceive themselves as low-risk individuals for HIV infection and thus are relatively less receptive to VMMC 4. The estimated low MC incidence in males aged 20–24 years can be associated with previous findings in which most VMMC clients in Tanzania were younger males, with about 76% of VMMC performed for males under 20 years of age in 2014 23 24…”
Section: Discussionmentioning
confidence: 64%
“…Multiple countries increased the proportion of males aged 15–29 years who were provided VMMC in 2016, when PEPFAR began emphasizing prioritizing VMMC in this age group to most immediately achieve the HIV preventive benefit of VMMC ( 8 ); however, the overall percentage of males aged 15–29 years who were circumcised declined in 2016. CDC continues to work with partners to identify and implement innovative approaches to increase VMMC demand among these men ( 9 ). The large proportion of VMMC clients aged <15 years also likely accounts for the lower HIV prevalence observed among VMMC clients compared with national estimates, ** because many of those aged <15 years likely had not yet had sexual intercourse, the primary mode of HIV transmission in this setting.…”
Section: Discussionmentioning
confidence: 99%